Osimertinib in the treatment of patients with epidermal growth factor receptor T790M mutation-positive metastatic non-small cell lung cancer: clinical trial evidence and experience. (December 2016) - Sullivan, Ivana; Planchard, David
Patients with advanced epidermal growth factor receptor ( EGFR ) mutant non-small cell lung cancer (NSCLC) are particularly sensitive to treatment with first- or second-generation EGFR tyrosine kinase inhibitors such as gefitinib, erlotinib and afatinib, which block the cell-signaling pathways that drive the growth of tumor cells. Unfortunately, the majority of patients develop resistance to them after a median duration of response of around 10 months, and in over half of these patients the emergence of the EGFR T790M resistance mutation is detected. Osimertinib is an oral, highly selective, irreversible inhibitor of both EGFR- activating mutations and the T790M-resistance mutation, while sparing the activity of wild-type EGFR . This article reviews clinical trial development of osimertinib in patients with NSCLC, presenting efficacy and safety evidence for its value in the EGFR T790M mutation-positive population and in different settings, including patients with metastatic disease. The preclinical background of clinically acquired resistance to osimertinib is presented and the combination tactics being investigated in an attempt to circumvent this are addressed.